New Research Trends in Transport Sustainability and Innovation TranSopot 2017 Conference (Springer Proceedings in Business and Economics,, 2018)
This proceedings volume examines the effects of transport on socio-economic development including innovation, public health and cultural behavior. Featuring contributions presented at the 2017 TranSopot Conference in Sopot, Poland, the enclosed papers are divided to provide emerging research in transport sustainability, innovation, structure, and in municipal transport economics. Collectively, the contributions provide not only the theoretical background for transport analysis but also empirical data and practical applications. Researchers in the transport sector strive to explore the nuances of various aspects of transport economics, which are connected on many levels. The sustainability of transport fits into a wide perspective of the sustainable economy. It treats the activities of individuals, companies and local, regional and national governments as means of achieving economic and social ends. Conversely, transport sustainability has a certain burden on society as it may generate external costs in the form of congestion, pollution and negative health effects. Many of these adverse effects might be counteracted by transport innovations, both the technical ones and the organizational ones. These innovations, while their main goal might be to increase the efficiency of the transport entities, should also fit into the desirable trend of responsible economic design thinking. These general ideas of transport research naturally have to influence the research in various branches of transport ranging from the road transport to railway. Lastly, there is the municipal transport, in which goals of different stakeholders are often contradictory which leads to highly complicated decision problems. Featuring case examples on topics as bike sharing, green travel, compact cars, freight transport and electric cars, this book will be of interest to researchers, practitioners, policy makers and students in the fields of transport economics, innovation, and sustainability.